Professor T. [Season 1] [videorecording (DVD)] - Miller, Ben, 1966-; White, Barney; Woodward, Sarah (PBS Distribution, 2021)
Jasper Tempest is a Professor of Criminology at Cambridge University. He is obsessed with cleanliness, structure and order, but his genius for solving crimes means he is constantly having to get his hands dirty, helping the police to crack their most difficult cases.